The Role of Perceived Burdensomeness and Thwarted Belongingness in Suicidal Ideation among University Undergraduates - Moses Adeleke Adeoye; Adekola Kami Lasisi (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Suicidal ideation is a significant concern among university students and understanding the factors that contribute to this distressing phenomenon is crucial for prevention and intervention efforts. Identifying the specific factors that contribute to suicidal thoughts and behaviors can tailor their interventions to address the unique needs of this population. This study aims to analyze relationship between perceived burdensomeness, thwarted belongingness and suicidal ideation among University undergraduates. The study is cross-sectional and uses a composite measure of suicidal behaviors. Three research questions and four hypotheses were raised to guide the study. The study used a quantitative research design to collect data from University undergraduates. A sample of 177 students participated in the study, completing self-report measures assessing perceived burdensomeness, thwarted belongingness and suicidal ideation. The participants completed questionnaires assessing their levels of perceived burdensomeness, thwarted belongingness and suicidal ideation. The study indicated that the prevalence of suicidal ideation among the participants was found to be moderate. This finding is significant as it highlights the importance of addressing feelings of burdensomeness to prevent suicidal ideation among university students.